2021
DOI: 10.1039/d0rp00266f
|View full text |Cite
|
Sign up to set email alerts
|

Students’ meaningful learning experiences from participating in organic chemistry writing-to-learn activities

Abstract: Teaching organic chemistry requires supporting learning strategies that meaningfully engage students with the challenging concepts and advanced problem-solving skills needed to be successful. Such meaningful learning experiences should encourage students to actively choose to incorporate new concepts into their existing knowledge frameworks by appealing to the cognitive, affective, and psychomotor domains of learning. This study provides a qualitative analysis of students’ meaningful learning experiences after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 58 publications
8
53
0
Order By: Relevance
“…That students made global revisions provides evidence that the WTL process encouraged reflection and revision for these students, an intended goal of WTL assignments (Hayes, 1996;Anderson et al, 2015;Gere et al, 2019). This result provides further evidence for the value of WTL in organic chemistry (Schmidt-McCormack et al, 2019;Watts et al, 2020;Gupte et al, 2021;Petterson et al, 2022), while extending the findings of prior studies by demonstrating students' engagement with WTL on a task that required consideration of two reaction mechanisms, represented by both the EPF and RCDs. Additionally, this finding provides evidence for using the WTL process with peer review and revision to support students' conceptual engagement within the organic chemistry course context.…”
Section: Students Largely Selected the Favoured Mechanistic Pathway A...supporting
confidence: 58%
See 1 more Smart Citation
“…That students made global revisions provides evidence that the WTL process encouraged reflection and revision for these students, an intended goal of WTL assignments (Hayes, 1996;Anderson et al, 2015;Gere et al, 2019). This result provides further evidence for the value of WTL in organic chemistry (Schmidt-McCormack et al, 2019;Watts et al, 2020;Gupte et al, 2021;Petterson et al, 2022), while extending the findings of prior studies by demonstrating students' engagement with WTL on a task that required consideration of two reaction mechanisms, represented by both the EPF and RCDs. Additionally, this finding provides evidence for using the WTL process with peer review and revision to support students' conceptual engagement within the organic chemistry course context.…”
Section: Students Largely Selected the Favoured Mechanistic Pathway A...supporting
confidence: 58%
“…However, studies do suggest that reading other students' work and providing feedback may have more influence on students' revisions compared to receiving feedback, in STEM courses (Finkenstaedt-Quinn et al, 2021a), writing courses (Lundstrom and Baker, 2009;Cho and MacArthur, 2010;Cho and Cho, 2011), and during hypothetical peer review (Berg and Moon, 2022). In addition to supporting students' conceptual learning, there is also evidence that peer review can support students' positive affective experiences with WTL assignments in a way that supports meaningful learning (Gupte et al, 2021;Petterson et al, 2022). With the existing evidence for the role of WTL with peer review and revision supporting students' learning, it is necessary to further explore WTL assignments and the peer review process in the context of students' reasoning with representations in organic chemistry, which is the goal of this study.…”
Section: Reasoning With Mechanistic Representations In Organic Chemistrymentioning
confidence: 99%
“…Additionally, for a subset of students, peer review and revision were perceived to be beneficial. These findings align with prior research on WTL in organic chemistry, [17,42] for which students similarly reported perceived learning benefits from engaging in writing, in particular discussing the beneficial roles of authentic contexts and peer review in supporting their learning.…”
Section: Student Perceptions Of Writing-to-learnsupporting
confidence: 87%
“…[6,14,15] This WTL process also aligns with cognitive theories of learning such as social constructivism, [1,6,10,14,15] which posits that students learn within their individual social environments by restructuring existing knowledge to incorporate new knowledge. [14,15] Indeed, research has shown that this WTL process has enabled students to constructively engage with the peer review and revision processes, [16,17] thereby supporting them in learning challenging content in a wide range of introductory STEM courses, including biology, chemistry, and statistics. [12,[18][19][20][21][22] Our WTL implementation also follows the principles for designing effective "writing to communicate" experiences in engineering, with writing assignments that include an authentic investigation and audience, are tied to the technical course content, and provide useful practice for engineering careers, while not being overly burdensome for the engineering faculty instructor.…”
Section: Introductionmentioning
confidence: 99%
“…Wright et al (2019) concluded that writing-to-learn is effective in the development of scientific literacy. Similarly, Gupte et al (2021) explained the effect of writingto-learn activities on students' meaningful learning. Balasundram and Karpudewan (2021), who aimed to improve students' concept learning through writing, combined writing-to-learn activities with technology, while Sintiawati, Sinega and Karim (2021) intended to improve students' concept learning and communication skills through the strategy of writing-to-learn.…”
Section: Writing-to-learn Modelmentioning
confidence: 99%